To solve this equation by elimination, what you would do is multiply one of the equations by -1, or distribute -1 to each term in the equation, any of the 2 equations. Then align the equations and add them together.
-(X + 3y = 3)
-X - 3y = -3
-X - 3y = -3
X + 6y = 3
__________
3y = 0
y = 0/3 = 0.
Now we can solve for x, by simply plugging the value of y into any of the 2 equations.
X + 6y = 3
X + 6(0) = 3
X + 0 = 3
X = 3.
The solution to your system of equations would be (3,0).
Check this by plugging in the point to the other equation and see if it is true.
X + 3y = 3
(3) + 3(0) = 3
3 + 0 = 3
3 = 3.
Thus it is the solution.
Answer:
![\large\boxed{ -4](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B%20-4%3Cx%3C%5Cfrac%7B1%7D%7B2%7D%5Cto%20x%5Cin%5Cleft%28-4%2C%5C%20%5Cdfrac%7B1%7D%7B2%7D%5Cright%29%7D)
Step-by-step explanation:
![Domain:\ 2x-1\neq0\to x\neq\dfrac{1}{2}](https://tex.z-dn.net/?f=Domain%3A%5C%202x-1%5Cneq0%5Cto%20x%5Cneq%5Cdfrac%7B1%7D%7B2%7D)
![\dfrac{x+4}{2x-1}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%2B4%7D%7B2x-1%7D%3C0%5Ciff%28x%2B4%29%282x-1%29%3C0%5C%5C%5C%5Cx%2B4%3D0%5Cqquad%5Ctext%7Bsubtract%204%20from%20both%20sides%7D%5C%5C%5C%5C%5Cboxed%7Bx%3D-4%7D%5C%5C%5C%5C2x-1%3D0%5Cqquad%5Ctext%7Badd%201%20to%20both%20sides%7D%5C%5C%5C%5C2x%3D1%5Cqquad%5Ctext%7Bdivide%20both%20side%20by%202%7D%5C%5C%5C%5C%5Cboxed%7Bx%3D%5Cdfrac%7B1%7D%7B2%7D%7D)
![(x+4)(2x-1)=(x)(2x)+....=2x^2+...\to 2>0\\\\\text{therefore the parabola is op}\text{en up}](https://tex.z-dn.net/?f=%28x%2B4%29%282x-1%29%3D%28x%29%282x%29%2B....%3D2x%5E2%2B...%5Cto%202%3E0%5C%5C%5C%5C%5Ctext%7Btherefore%20the%20parabola%20is%20op%7D%5Ctext%7Ben%20up%7D)
![\text{Look at the picture.}](https://tex.z-dn.net/?f=%5Ctext%7BLook%20at%20the%20picture.%7D)
![\dfrac{x+4}{2x-1}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%2B4%7D%7B2x-1%7D%3C0%5Ciff%20-4%3Cx%3C%5Cfrac%7B1%7D%7B2%7D%5Cto%20x%5Cin%5Cleft%28-4%2C%5C%20%5Cdfrac%7B1%7D%7B2%7D%5Cright%29)
Answer:
x = 5/2
Step-by-step explanation:
So firstly, you want to distribute. It'll make your life much easier.
-2x + 8 = 3
-2x = -5 (subtracting 8 from both sides)
x = 5/2 (dividing both sides by -2 to obtain x)
Hope this helps :)
Answer:
if you turn it sideways it looks like an acute so i think it will be 60* or 61* i am not sure
Step-by-step explanation: